Harmony of Food Security: A Study of the Legal Basis of Agrarian Law in Supporting Food Self-Sufficiency in Ngawi District - Heru Drajat Sulistyo; Meiyana Hikmawati; Hari Soeseno Hardjoloekito (Riviera Publishing, 2024)
Food is a basic need that must be fulfilled. In general, food availability that is smaller than the needs can cause instability in society. Indonesia is an agrarian country, whose source of livelihood is through agriculture, plantations and fisheries. This means that, objectively, Indonesia's food security rests on these three sources. The legal basis and foundation related to agrarian policy or land reform have basically been carried out for a long time, starting from President Soekarno to President Joko Widodo. However, its implementation is not as easy as turning the palm of the hand. The purpose of this research is to objectively assess the harmonization of food security through agrarian law policies in food self-sufficiency in Ngawi Regency. Data collection techniques used observation and documents with source triangulation. Meanwhile, data analysis uses the stages of reduction, presentation of data, drawing and validating conclusions. Type of field research, with descriptive qualitative method. The results found that the implementation of agrarian law policy in Ngawi Regency has been optimally successful. Food security in Ngawi Regency has proven to be able to overcome social, health and economic problems in addition to problems related to production. Ngawi District has the capacity to produce food but is unable to guarantee food security, as seen from the various achievements of Ngawi District in food security, as well as being named the best district in agriculture nationally. Legal policies ranging from UUPA, agrarian law to regional policies that regulate and support regional potential in agriculture.